Performing Music History
XXIV, 362 p. 63 illus., 39 illus. in color.
Keywords: Performing Music History offers a unique perspective on music history and performance through a series of conversations with women and men intimately associated with music performance, history, and practice: the musicians themselves. Fifty-five celebrated artists—singers, pianists, violinists, cellists, flutists, horn players, oboists, composers, conductors, and jazz greats—provide interviews that encompass most of Western music history, from the Middle Ages to contemporary classical music, avant-garde innovations, and Broadway musicals. The book covers music history through lenses that include “authentic” performance, original instrumentation, and social context. Moreover, the musicians interviewed all bring to bear upon their respective subjects three outstanding qualities: 1) their high esteem in the music world as immediately recognizable names among musicians and public alike; 2) their energy and devotion to scholarship and the recovery of endangered musical heritages; and 3) their considerable skills, media savvy, and showmanship as communicators. Introductory essays to each chapter provide brief synopses of historical eras and topics. Combining careful scholarship and lively conversation, Performing Music History explores historical contexts for a host of fascinating issues.